Evaluation of macular and retinal nerve fiber layer thicknesses in episodic-type cluster headache patients by optical coherence tomography (Annals of Medical Research, 2021)
None
Keywords: Cluster Headache; Optical Coherence Tomography; Macular Thickness; Retinal Nerve Fiber Layer Thickness.